Kesulitan Siswa dalam Menyelesaikan Soal Cerita Matematika pada Materi Perkalian Bilangan Bulat Kelas III UPT SDN 200 Gresik - Laila, Hanifa Nur; Yustitia, Via (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Students’ abilities are low in multiplication material, especially in math story problems. This will cause difficulties in solving story problems, students will experience difficulties and mistakes because students are not careful in reading and understanding sentence by sentence. The aim of this research is to describe what difficulties students experience in solving mathematics story problems and the efforts that can be made to overcome these students' difficulties. This research uses a descriptive method with a qualitative approach. The subjects of this research were 3 class III students at UPT SDN 200 Gresik who were selected based on test results by dividing the criteria as high, medium and low. The data collection techniques used were written tests, interviews and documentation. Meanwhile, for the validity of the data using triangulation, based on the research results, there are still many students who have difficulty working on math story problems. It was found that students who had difficulties generally belonged to students who did not master good problem solving and determining arithmetic operations that were appropriate to the problems in math story problems. According to findings in the field, it can be concluded that students have several difficulties (1) difficulty understanding concepts, (2) difficulties in calculations (3) process skills